THE ROLE OF BRAND ATTITUDE AND BRAND CREDIBILITY AS A MEDIATOR OF THE CELEBRITY ENDORSEMENT STRATEGY TO GENERATE PURCHASE INTENTION - Vidyanata, Deandra; Sunaryo, Sunaryo; Hadiwidjojo, Djumilah (Jurnal Aplikasi Manajemen, 2018)
The growth of Instagram continues, with the majority of its users being millennial consumers who share all aspects of their life on social media. One of the most popular advertising strategies is using celebrity endorsers. The purpose of this study is to investigate the role of brand attitude and brand credibility as a mediator of the celebrity endorsement to purchase intention. This study can be categorized as explanatory research and the sampling technique used in this research is purposive sampling. The result of this study showed that celebrity endorsement would not directly affect purchase intention, though celebrity endorsement can enhance brand attitude and brand credibility which in turn increase purchase intention.This study only focused on apparel products. Thus future research may consider using another type of product. Further, future research is expected to use another social media other than Instagram and to consider using another variable as the mediator.